Biochemical fingerprints of human papillomavirus infection and cervical dysplasia using cervical fluids: Spectral pattern investigation. Issue 10 (20th July 2016) - Kim, Yeon‐Hee; Chang, Boksoon; Choi, Jeong‐Hyun; Park, Hun‐Kuk; Choi, Samjin
Abstract: The Pap smear is the primary screening tool for invasive cervical cancer resulting from a persistent infection with oncogenic human papillomavirus (HPV); however, there are the problems such as the inability to distinguish between HPV infection and cervical dysplasia and a low sensitivity remain. We present preliminary findings of a label‐free method to detect and classify HPV infection and cervical dysplasia using human cervical fluids. Three experimental groups, defined as normal, HPV‐positive, and cervical dysplasia, were evaluated through their Raman spectral patterns for noise‐independence, high reproducibility, and uniformity. Clinical diagnosis was performed through liquid‐based cervical cytology, HPV test, and cervical histologic examination. Healthy cervical fluids showed a strong Raman intensity at 877 cm −1 (symmetric C–C stretching), and at 963 cm −1 (phosphate), compared to a reference Raman peak at 1003 cm −1 (phenylalanine symmetric ring breath). The HPV‐positive cervical fluids showed a strong intensity of a Raman peak at 1448 cm −1 corresponding to C–H deformation vibration mode and the highest similarity between the central and ring zones among the three groups. The cervical dysplasia fluids showed the presence of strong peaks compared to the control and HPV‐positive groups. In addition, different Raman spectra were acquired according to HPV type. Therefore, all ranges of cervical fluid‐induced Raman spectra could be used to detect the presence of cervical pre‐cancer. Raman peak‐gated assessment provides a label‐free and nondestructive tool for the clinical diagnosis of HPV infection and cervical precancerous changes.